ROOM BOOKING THROUGH ONLINE TRAVEL AGENT AT ASTON HOTEL PALEMBANG - Permatasari, Mustika; Silvia, Mega; Setiawan, Mulkan (Universitas Bunda Mulia, 2024)
Online Travel Agent is an internet-based platform that assists guests in booking hotel rooms. When a guest books a room through an Online Travel Agent, the booking will usually be directly accepted by the hotel if the hotel reservation department still opens the room booking service from the online travel agent. But on the other hand, if the reservation department has closed the online travel agent for booking rooms, guests automatically cannot book rooms because the hotel rooms are fully occupied. The high percentage of room bookings that have exceeded the percentage of sales through online travel agents at Hotel Aston Palembang has caused problems such as overbooking through online travel agents in the reservation department, causing guests who have come and have booked rooms through online travel agents but do not get rooms when checking in due to high occupancy rates. The purpose of this study is to determine the Standard Operating Procedure (SOP) in handling room reservations through the Online Travel Agent, the availability of supporting equipment for handling room reservations through the Online Travel Agent and the ability of staff in handling room reservations through the Online Travel Agent. The research method used is a qualitative approach with descriptive methods. Data collection techniques in this qualitative research use observation and interviews. The reservation officer has implemented the Standard operational procedure for booking rooms properly but there are several things that are still not done by the reservation officer such as not confirming in detail the size of the guest bed and not closing the reservation allotment when the hotel is fully booked so that room overbooking occurs and becomes a guest complaint when checking in at Hotel Aston Palembang.